التخطيط التأشيري (الإطار النظري والعملي) - هرمز, نور الدين; صقر, محمد; سلامة, باسل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
سوف نستعرض في هذه الدراسة أسلوب التخطيط التأشيري الذي يعتبر أحد الأساليب المستخدمة في إدارة الاقتصاد الوطني وإيجاد نوع من التعاون بين الدولة والقطاع الخاص للوصول إلى أكبر درجة من التفاهم والانسجام الذي يصب في تحقيق مصلحة الاقتصاد الوطني وتتضمن هذه الدراسة قسمين : - الجانب النظري لهذا الأسلوب: حيث سيتم تبيان ماهية التخطيط التأشيري، ومدى مواكبته للتغيرات الاقتصادية والاجتماعية في الاقتصاد، بالإضافة إلى النظريات الاقتصادية التي تدعم هذا الأسلوب. - الجانب العملي الذي يتضمن التجربة الفرنسية في تطبيق هذا الأسلوب: حيث نبين فيه تطور الخطط الفرنسية وطرق تطبيقها لهذا الأسلوب واستخلاص الطرق التي يعتمد عليها هذا الأسلوب من الناحية العملية، وما الذي يحتاجه هذا الأسلوب من إعداد الخطط الاقتصادية في فرنسا. In this study we expose the style of indicative planning which is considered one ways employed in managing national economy. It can also help us to find a kind of co-operation between the government and private sector in order to achieve the greatest degree of harmony and understanding which will do good for national economy. This study includes two parts. In the theoretical part, we see what is indicative planning, and extent to which it goes with economic and social mutations in the economy, in addition to economic theory which backs this style. In the practical part, we include the development of French plans, and the methods using this style and decocting the methods, on which this style depends from practical way, and what is need to set up French plan.